Bibliometric and visual analysis of neutrophil extracellular traps from 2004 to 2022 - Wan, Yantong; Shen, Junyi; Ouyang, Jiafu; Dong, Peng; Hong, Yinghao; Liang, Lixin; Liu, Jinghua (Frontiers in Immunology, 2022)
Background: Neutrophil extracellular traps (NETs) are specialized structures formed by neutrophils that were initially found to be important in killing pathogenic bacteria during infection. With the development of related research, the relationship between NETs and diseases such as sepsis, cancer, and systemic lupus erythematosus has received close attention. However, there is a lack of reports that comprehensively and objectively present the current status of NETs-related studies. Therefore, this study aims to visually analyze the current status and trends of NETs-related research by means of bibliometrics and knowledge mapping. Methods: NETs-related articles and reviews were retrieved using the Web of Science core collection subject search, and bibliometric analysis was performed in Excel 365, CiteSpace, VOSviewer, and Bibliometrix (R-Tool of R-Studio). Results: A total of 4866 publications from 2004 to 2022 were included in the bibliometric analysis. The number of publications showed an increasing trend from year to year. Collaborative network analysis showed that the United States and Germany were the most influential countries in this field, with the highest number of publications and citations. The journal with the most publications was Frontiers in Immunology. Brinkmann Volker is an authoritative author in this field, and his publication "Neutrophil extracellular traps kill bacteria" was the most frequently cited. The literature and keyword analysis shows that the relationship between NETs and diseases (hematological diseases, sepsis, cancer, etc.) and cell death (apoptosis, necrosis, scorching, etc.) is a popular research topic. Currently, NETs and SARS-CoV-2-related studies are at the forefront of the field. Conclusion: This study is the first to visualize the research in NETs-related fields using bibliometric methods, revealing the trends and frontiers of NETs research. This study will provide valuable references for scholars to find research focus questions and partners.